Role of the Intestinal Epithelium and Its Interaction With the Microbiota in Food Allergy - Ali, Ayesha; Tan, HuiYing; Kaiko, Gerard E. (Frontiers in Immunology, 2020)
The intestinal epithelial tract forms a dynamic lining of the digestive system consisting of a range of epithelial cell sub-types with diverse functions fulfilling specific niches. The intestinal epithelium is more than just a physical barrier regulating nutrient uptake, rather it plays a critical role in homeostasis through its intrinsic innate immune function, pivotal regulation of antigen sensitization, and a bi-directional interplay with the microbiota that evolves with age. In this review we will discuss these functions of the epithelium in the context of food allergy.